2017
DOI: 10.15171/joddd.2017.002
|View full text |Cite
|
Sign up to set email alerts
|

The color masking ability of a zirconia ceramic on the substrates with different values

Abstract: Background. The color masking ability of a restoration plays a significant role in coveringa discolored substructure; however, this optical property of zirconia ceramics has not been clearly determined yet. The aim of this in vitro study was to evaluate the color masking ability of a zirconia ceramic on substrates with different values.Methods. Ten zirconia disk specimens,0.5 mm in thickness and 10 mm in diameter, were fabricated by a CAD/CAM system. Four substrates with different values were prepared, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Oh and Kim advocated not to apply a gold alloy background for zirconia restorations due to color mismatches. Negative effects of black and gray backgrounds on the color of thin zirconia ceramics (≤0.5 mm) have been reported . Wang et al reported TPs of zirconia ceramic ranging between 5.5 and 15.1, indicating the background effect on translucency.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Oh and Kim advocated not to apply a gold alloy background for zirconia restorations due to color mismatches. Negative effects of black and gray backgrounds on the color of thin zirconia ceramics (≤0.5 mm) have been reported . Wang et al reported TPs of zirconia ceramic ranging between 5.5 and 15.1, indicating the background effect on translucency.…”
Section: Clinical Factorsmentioning
confidence: 99%
“…Tabatabaian et al evaluated the masking ability of a zirconia ceramic on a black and white substrate and defined a minimum thickness of 1 mm for acceptable masking ability and a minimum thickness of 1.6 mm for ideal masking ability. Tabatabaian et al indicated that a 0.5 mm framework zirconia could not show adequate color masking ability to hide grey and black substrates. Basso et al revealed that monolithic lithium disilicate‐based veneers with 0.7 to 2 mm thicknesses masked C4‐shaded substrate but could not mask metallic substrates, while bilayer structures with 0.5 mm zirconia copings and the same veneers exhibited greater shade masking ability than the monolithic structures .…”
Section: Substratementioning
confidence: 99%
“…21 The background L * value affects the masking ability of an 0.5-mm-thick white zirconia ceramic. 22 A zirconia-based restoration commonly includes a 0.3- to 0.5-mm-thick zirconia coping and a 1-mm-thick veneering porcelain. Although an 0.4-mm-thick zirconia coping alone produces acceptable masking ability on tooth-colored backgrounds, it might be insufficient for masking metal backgrounds.…”
Section: Introductionmentioning
confidence: 99%